Comparison of Fatty Acid Compositions of Commercial Fish and Fish By-Products Oils Used in Fish Feed Industry in Turkey - Kutsal Gamsız; Ali Yıldırım Korkut; Aysun Kop (Turkish Journal of Agriculture: Food Science and Technology)
Fats have a function in transmitting the necessary fatty acids to fish as well as being an energy source in fish nutrition. In particular, high-chain unsaturated fatty acids are needed for feeding saltwater fish. In this study, the fatty acid composition of fish oils obtained from some whole-body fish and fish by-products used in the fish-feed industry in Turkey was determined and compared with each other. Accordingly, SFA (Saturated fatty acids) ratios were in the range of 15.57-33.38% in the oils obtained from the whole-body fish and in the range of 16.3-31.89% in the oils from fish by-products; MUFA (Monounsaturated fatty acids) ratios were in the range of 24-38.69% in the oils obtained from the whole-body fish and in the range of 25.81-47.57% in the oils from fish by-products; PUFA (Polyunsaturated fatty acids) ratios were in the range of 31-36.73% in the oils obtained from the whole-body fish and in the range of 33.54-36.78% in the oils from fish by-products. Given DHA (docosahexaenoic acid) and EPA (eicosapentaenoic acid) ratios which are among the most important PUFAs for nutrition, it was determined that DHA ratios were in the range of 14.08-19.10% in the oils obtained from the whole-body fish and in the range of 3.55-15.28% in the oils from fish by-products, whereas EPA ratios were in the range of 8-9.89% in the oils obtained from the whole-body fish and in the range of 2.63-15.28% in the oils from fish by-products.